Target next-generation sequencing for the accurate diagnosis of Parvimonas micra lung abscess: a case series and literature review - Zhang, Dongmei; Fan, Boyang; Yang, Yuan; Jiang, Chunguo; An, Li; Wang, Xue; He, Hangyong (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundParvimonas micra (P. micra) has been identified as a pathogen capable of causing lung abscesses; however, its identification poses challenges due to the specialized culture conditions for anaerobic bacterial isolation. Only a few cases of lung abscesses caused by P. micra infection have been reported. Therefore, we describe the clinical characteristics of lung abscesses due to P. micra based on our case series.MethodsA retrospective analysis was conducted on eight patients who were diagnosed with lung abscesses attributed to P. micra. Detection of P. micra was accomplished through target next-generation sequencing (tNGS). A systematic search of the PubMed database using keywords “lung abscess” and “Parvimonas micra/Peptostreptococcus micros” was performed to review published literature pertaining to similar cases.ResultsAmong the eight patients reviewed, all exhibited poor oral hygiene, with four presenting with comorbid diabetes. Chest computed tomography (CT) showed high-density mass shadows with necrosis and small cavities in the middle. Bronchoscopic examination revealed purulent sputum and bronchial mucosal inflammation. Thick secretions obstructed the airway, leading to the poor drainage of pus, and the formation of local abscesses leading to irresponsive to antibiotic therapy, which finally protracted recovery time. P. micra was successfully identified in bronchoalveolar lavage fluid (BALF) samples from all eight patients using tNGS; in contrast, sputum and BALF bacterial cultures yielded negative results, with P. micra cultured from only one empyema sample. Following appropriate antibiotic therapy, seven patients recovered. In previously documented cases, favorable outcomes were observed in 77.8% of individuals treated with antibiotics and 22.2% were cured after surgical interventions for P. micra lung abscesses.ConclusionsThis study enriches our understanding of the clinical characteristics associated with lung abscesses attributed to P. micra. Importantly, tNGS has emerged as a rapid and effective diagnostic test in scenarios where traditional sputum cultures are negative. Encouragingly, patients with lung abscesses caused by P. micra infection exhibit a favorable prognosis with effective airway clearance and judicious anti-infective management.